THE EFFECT OF STIRRING SPEED AND COLLECTOR CONCENTRATION ON NICKEL RECOVERY FROM PYROPHYLLITE USING FROTH FLOTATION - Hanifah Rifki Sakib Thalib; Sandra Santosa; Mas'udah Mas'udah (Politeknik Negeri Malang, 2023)
Nickel is an important element in the metal alloy industry. In Indonesia, nickel resources are found in many areas in the form of rocks such as pyrophyllite. Froth flotation is a method commonly used in the mining industry to extract metals such as nickel from mineral rocks. However, the nickel concentrates yield tends to be relatively low. This is often influenced by several factors such as the stirring speed and the concentration of the collector used in the process. Therefore, this study aims to investigate the effect of agitation speed and collector concentration on the nickel recovery results obtained from the froth flotation process. In this study, variations of stirring speed at 500, 600, and 750 rpm were used. Meanwhile, the collector concentration varied to 2,5%, 4,5% and 6,5%. The results showed that the stirring speed and collector concentration had a significant impact on nickel recovery. Optimum results were obtained at 750 rpm and 6,5% where the nickel concentration reached 2,475% from the initial concentration of 8,21%.